Association of circulating irisin levels with normal weight obesity, glycemic and lipid profile. Issue 1 (December 2015) - Mehrabian, Sarvenaz; Taheri, Ehsaneh; Karkhaneh, Maryam; Qorbani, Mostafa; Hosseini, Saeed
Abstract Background Irisin, a recently identified myokine/adipokine, has potential role in type 2 diabetes and obesity. Normal weight obesity (NWO) is associated with a significantly higher risk of developing metabolic syndrome and cardiometabolic dysfunction. The aim of this study was to investigate association of irisin level with NWO, glycemicand lipid profile in women. Methods In this matchedcase-control study, 38 subjects with NWO (body mass index (BMI) <25 kg/m2 and BF % > 30) as case and 26 controls (BMI <25 kg/m2 and BF % < 30) were selected randomly from sport clubs in the East area of Tehran, Iran. In addition to anthropometric variables, including BMI and body composition, fasting blood sugar (FBS), fasting levels of irisin andinsulin, triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL) and low-density lipoprotein (LDL) cholesterol were measured. All statistical analyses were performed with SPSS 18.0. Results In univariate analysis, levels of irisin were significantly higher in subjects with NWO compared to controls (0.81 ± 0.41vs. 0.58 ± 0.26 ng/ml, P  = 0.009). This association remained significant after adjusting for confounders (adjusted for energy intake, physical activity, waist circumference and BMI) (P  = 0.049). In NWO, irisin level was not significantly correlated with all glycemic and lipid profile. In control group, only correlation ofirisin with insulin was statistically significant (P  = 0.03). Conclusion Serum irisin levels were higher in NWO subjects than controls. In control group, only the negative association between irisin and insulin levels was statistically significant. Further studies with larger sample size are clearly needed to evaluate the potential role of irisin in NWO subject and other disturbed metabolic conditions.